PENGARUH LULUSAN PERGURUANTINGGI DAN TENAGA KERJA TERAMPIL TERHADAP TINGKAT PENGANGGURAN DI KOTA PALEMBANG - Arga Sihotang; Yos Karimudin (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
College graduates and high school graduates are one of the contributors to the formation of the unemployment rate. The bargaining power of these graduates in the world of work is still low, this is because the quality and ability of young people to enter the world of work is still minimal, so companies are very selective in getting the workforce they need. This study will look at the influence of college graduates and skilled labor on the unemployment rate in Palembang City. This research uses primary and secondary data types. Primary data were collected and researched directly from informal sector migrant workers through structured questions that were collected using a questionnaire. Primary data collected includes aspects of the source of the goods. Secondary data includes data and information obtained from data whose data sources are obtained from: Official publications of the Indonesian Central Statistics Agency (BPS), official publications of the Central Statistics Agency (BPS. South Sumatra Province), National Socio-Economic Survey (SUSENAS), Publications from the Ministry of Energy Work and Transmigration, National Newspaper Media Publications, National Labor Force Survey (SAKERNAS), and from various papers, journals, scientific papers, literature books deemed relevant to this research. To determine the level of closeness of the relationship between the independent variable simultaneously and the dependent variable, multiple correlation (R) is used. To find out how much the relationship between the independent variables simultaneously to the dependent variable will be seen from R2. Based on the research results, there is a significant relationship between college graduates and skilled workers and the unemployment rate in Palembang City. These results are obtained from testing the hypothesis being tested where the hypothesis can be accepted. Also, there is a significant relationship between college graduates and the level of community unemployment in Palembang City. These results are obtained from testing the tested hypotheses where the hypothesis can be accepted.